2013
DOI: 10.1111/camh.12042
|View full text |Cite
|
Sign up to set email alerts
|

Does family drawing assess attachment representations of late‐adopted children? A preliminary report

Abstract: Background Attachment representations of late‐adopted children have usually been measured by attachment narratives or observational procedures. Recently an attachment‐based coding system for family drawings was developed by attachment researchers and it was used both with clinical and nonclinical samples, but it has never been used with adoptees. Method This study examined the differences between attachment representations of 29 late‐adopted children aged 5–7 years (M = 6.35, 51.7% girls) and 12 non‐adopted pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
25
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
1
25
0
1
Order By: Relevance
“…Some of the children raised in institutions suffer from a severe socioemotional deprivation and do not form attachments towards their institutional caregivers (Smyke et al 2002;Zeanah et al 2005). Adopted children have been described as showing reactive attachment disorders and indiscriminate friendly behavior (Zeanah 2000;Zeanah et al 2004): adverse preadoption rearing settings can, therefore, lead to insecure or disorganized attachment representations (Chisholm et al 1995;Hodges et al 2011;Pace et al 2014;Pace et al 2015a;Palacios et al 2005;van IJzendoorn and Juffer 2006;Vorria et al 2003), which, in turn, can result in adverse developmental outcomes (Juffer and van IJzendoorn 2005;Van den Dries et al 2009;van IJzendoorn et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some of the children raised in institutions suffer from a severe socioemotional deprivation and do not form attachments towards their institutional caregivers (Smyke et al 2002;Zeanah et al 2005). Adopted children have been described as showing reactive attachment disorders and indiscriminate friendly behavior (Zeanah 2000;Zeanah et al 2004): adverse preadoption rearing settings can, therefore, lead to insecure or disorganized attachment representations (Chisholm et al 1995;Hodges et al 2011;Pace et al 2014;Pace et al 2015a;Palacios et al 2005;van IJzendoorn and Juffer 2006;Vorria et al 2003), which, in turn, can result in adverse developmental outcomes (Juffer and van IJzendoorn 2005;Van den Dries et al 2009;van IJzendoorn et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Families who adopt children -in particular older ones -often have to face their damaged attachment representations due to neglect, abandonment, and loss often experienced in their pre-adoption lives (Dozier & Rutter, 2008;Pace, Zavattini, & Tambelli, 2015). A 2009 meta-analysis showed that children adopted before 12 months of age were as securely attached as their non-adopted peers, whereas children adopted after their first birthday showed less attachment security if compared with non-adopted children (van den Dries, Juffer, van IJzendoorn, & Bakermans-Kranenburg, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The establishment of a secure attachment to the adoptive parents can mitigate the impact of early adversity experiences on these adolescents (Barcons et al, 2012;Bernedo, Fuentes, Fernández-Molina, & Bersabé, 2007;Feeney et al, 2007; van den Dries et al, 2009;Whitten & Weaver, 2010). Thus, adoption can function as a successful intervention (van IJzendoorn & Juffer, 2006) by providing children, who could not grow up with their birth parents, with the opportunity of developing a secure attachment relationship with their adoptive parents, and also promoting their cognitive development and psychological adjustment (Juffer et al, 2011;Pace, Zavattini, & Tambelli, 2015;Palacios, Román, Moreno, León, & Peñarrubia, 2014). Despite research showing that adopted adolescents have lower quality attachment relationships when compared to peers who had never been separated from their birth families, it also seems clear that, when comparing adopted children with institutionalized ones, there is a large socioemotional recovery after adoption, as the results presented by adopted children are far superior to the results shown by institutionalized children (Soares et al, 2014;Zeanah, Smyke, Koga, Carlson, & the BEIP Core Group, 2005).…”
mentioning
confidence: 99%